2021
DOI: 10.1016/j.medcle.2021.01.012
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection: A predisposing factor for acute coronary syndrome

Abstract: Introduction Several case series of ACS have been reported in COVID 19 patients. We aim to study its incidence, characteristics, and three-month prognosis. To put this incidence in perspective we compared it with the incidence of in-hospital ACS during the same period of 2019. Methods Observational multicenter cohort study of 3.108 COVID-19 patients admitted to two hospitals in Madrid between March 1st and May 15th, 2020. Ten patients suffered an ACS while being hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…[ 36 ]; [ 37 ]; [ 38 ]; [ 39 ]; [ 40 ]; [ 41 ]; [ 42 ]; [ 43 ]; [ 44 ]; [ 45 ]; [ 46 ]; [ 47 ]; [ 48 ].…”
Section: Uncited Referencesunclassified
“…[ 36 ]; [ 37 ]; [ 38 ]; [ 39 ]; [ 40 ]; [ 41 ]; [ 42 ]; [ 43 ]; [ 44 ]; [ 45 ]; [ 46 ]; [ 47 ]; [ 48 ].…”
Section: Uncited Referencesunclassified
“…La infección por dicho virus podría actuar como un factor desencadenante para empeorar la afección y provocar la muerte (17,51) . Los mecanismos subyacentes al SCA inducido por COVID-19 pueden incluir rotura de placa, espasmo coronario o microtrombos, debido a inflamación sistémica y tormenta de citocinas (52) .…”
Section: Síndrome Coronario Agudounclassified
“…Studies have shown that 7–36% of patients with COVID-19 infection develop myocardial injury [ 15 , 16 , 17 ]. The results of an observational multicenter cohort study (performed on 3108 COVID-19 patients) also showed an increase in the incidence of ACS in the COVID-19 era, compared to before the COVID-19 era (3.31% in 2020 and 1.01% in 2019) ( p < 0.013) [ 18 ]. Katsoularis I. et al suggested that the results of their study (86,742 patients with COVID-19 in the self-controlled case series and 348 481 matched control individuals in the matched cohort study) indicate that COVID-19 is a risk factor for AMI and ischemic stroke.…”
Section: Epidemiology and Etiology Of Acs In Covid-19mentioning
confidence: 99%
“…COVID-19 patients with ACS are more likely to have a more severe form of infection, and they have a mortality rate of up to 30%. The rehospitalization rate is very high (up to 20%) within the three months of follow-up [ 18 ]. The results of an observational cohort study (12,958 AMI patients) (519 COVID-19 positive) also showed that patients with COVID-19 and ACS had higher in-hospital (OR: 3.27; 95% (CI): 2.41–4.42) and thirty-day (OR: 6.53, 95% CI: 5.1–8.36) mortality, compared to patients with ACS without a diagnosis of COVID-19 [ 101 ].…”
Section: Impact Of Covid-19 On Mortality From Amimentioning
confidence: 99%